The Accuracy of Digital Radiography for Diagnosis of Fishbone Foreign Bodies in the Throat - Kasemsiri,Pornthep (2017)
Abstract Introduction Some patients with a fishbone as a foreign body of difficult diagnosis may require further investigations. Generally, radiography is used as the first choice for finding the fishbone. Objective The objective of this study is to determine the accuracy of digital radiography for diagnosis of fishbone foreign body in the throat Methods This descriptive experimental study design has three phases. In the first phase, we assessed subject contrast and visibility of fishbone on a homogeneous background; as for the second phase, we evaluated the embedded fishbone in the fresh cadaver’s throat. In the last phase, we studied the accuracy of radiography in diagnosing the fishbone foreign body at any site of the cadaver’s throat. Results The subject contrast of 15 fishbones ranged from 0.94 to 0.99. All types of fishbone were obvious in the first phase, whereas, in the second phase, visibility of fishbone was varied. The subject contrast and diameter of fishbone did not show statistically significant correlation with visibility (p = 0.09 and p = 0.24, respectively). In the third phase, embedded fishbone in the base of tongue was detected with the highest accuracy (sensitivity of 1.00 (95%CI: 0.44-1.00) and specificity of 0.92 (95%CI: 0.65-0.99)); whereas, the tonsil was of difficult interpretation with poorest diagnostic value (sensitivity of 0.00 (95%CI: 0.00-0.56) and specificity of 1.00 (95%CI: 0.76-1.00)). Conclusion The digital radiography provides the highest accuracy and benefit to the diagnosis of a fishbone foreign body at the base of the tongue; whereas, the tonsil was of difficult interpretation.